Epidermal Tattoo Patch for Ultrasound‐Based Transdermal Microballistic Delivery. Issue 12 (12th October 2017) - Soto, Fernando; Mishra, Rupesh K.; Chrostowski, Robert; Martin, Aida; Wang, Joseph
Abstract: This work presents a flexible transdermal tattoo patch with a novel penetrative ultrasound‐triggered microballistic delivery capability toward enhanced skin penetration of its microdose payload. The new microballistic transdermal patch consists of a microporous membrane attached on an elastic temporary tattoo designed to conform to the skin surface and resist repeated common mechanical strains characteristic of epidermal wear. The porous membrane contains cylindrical micropores, which are fully loaded with a microdose of a model cargo along with a perfluorocarbon emulsion. Application of a high intensity focused ultrasound pulse vaporizes the perfluorocarbon emulsion, which serves as a propellant for the rapid ejection of the encapsulated payload and its penetration into soft adherent surfaces. The utility of the new microballistic concept and advantages over passive diffusion are illustrated using a skin‐mimicking phantom model toward enhanced drug delivery and improved nerve agent decontamination. The marriage between wearable epidermal tattoo‐patch technology and penetrative needle‐free ultrasound‐microballistic processes paves the way for new skin‐worn delivery devices for diverse therapeutic, detoxification, and skin‐care applications. Abstract : A flexible epidermal tattoo patch for ultrasound‐triggered microballistic transdermal cargo delivery . The patch contains microcannons loaded with the desired payload and perfluorocarbon (firing) emulsion. Upon application of an ultrasound pulse, the payload is rapidly ejected toward deep tissue penetration. The utility of the new microballistic concept is illustrated toward enhanced drug delivery and chemical decontamination.